Contrast doppler echocardiography - P. NIEDERLE; P. FRÍDL; E. KOUDELKOVÁ; P. JEBAVÝ; M. HACO (Archives of Acoustics)
A new technique in the scope of cardiac ultrasound — "contrast Doppler echocardiography" — is introduced and its first clinical applications are presented. The presence of contrast material within the right heart cavities following the peripheral vein injection is easily recognized by characteristic Doppler signal changes. This knowledge was used to detect a small amount of contrast passing through atrial (ASD) or ventricular septal defect (VSD) towards the left heart cavities despite the dominant left-to-right shunting. The high sensitivity of contrast Doppler in those conditions was presented by correct diagnosis of 10 ASD and 3 VSD. Besides that, the other application of this technique is in selected cases of tricuspid regurgitation. Therefore, the combination of both pulsed Doppler and contrast echo-in-vestigation seems to be advantageous in the diagnosis of the mentioned diseases. However, further research in this very specialized method is required.